Modeling and Optimizing a New Culture Medium for In Vitro Rooting of G×N15 Prunus Rootstock using Artificial Neural Network-Genetic Algorithm - Arab, Mohammad Mehdi; Yadollahi, Abbas; Eftekhari, Maliheh; Ahmadi, Hamed; Akbari, Mohammad; Khorami, Saadat Sarikhani (Scientific reports, 2018)
The main aim of the present investigation is modeling and optimization of a new culture medium for in vitro rooting of G×N15 rootstock using an artificial neural network-genetic algorithm (ANN-GA). Six experiments for assessing different media culture, various concentrations of Indole – 3- butyric acid, different concentrations of Thiamine and Fe-EDDHA were designed. The effects of five ionic macronutrients (NH 4 + , NO 3 − , Ca 2+ , K + and Cl − ) on five growth parameters [root number (RN), root length (RL), root percentage (R%), fresh (FW) and dry weight (DW)] were evaluated using the ANN-GA method. The R 2 correlation values of 0.88, 0.88, 0.98, 0.94 and 0.87 between observed and predicted values were acquired for all five growth parameters, respectively. The ANN-GA results indicated that among the input variables, K + (7.6) and NH4 + (4.4), K + (7.7) and Ca 2+ (2.8), K + (36.7) and NH 4 + (4.3), K + (14.7) and NH 4 + (4.4) and K + (7.6) and NH 4 + (4.3) had the highest values of variable sensitivity ratio (VSR) in the data set, for RN, RL, R%, FW and DW, respectively. ANN-GA optimized LS medium for G×N15 rooting contained optimized amounts of 1 mg L −1 IBA, 100, 150, or 200 mg L −1 Fe-EDDHA and 1.6 mg L −1 Thiamine. The efficiency of the optimized culture media was compared to other standard media for Prunus rooting and the results indicated that the optimized medium is more efficient than the others.